(untitled) (Perner’s Contacts, 2011)
The contribution pays attention to a methodology of constructing robust plans related to resource scheduling within service systems using support of computer simulation. Simulation helps (reflecting defined criteria) with production of an initial (i) plan of project – i.e. time quotation of all service activities and (ii) schedule of service resources. The obtained plan and schedule represent a base for making series of random trials (using Monte Carlo method) with the goal to create optimal (or rather suitable suboptimal) plan of project and schedule of resources.